A review of the louse genus Tinamotaecola (Insecta: Phthiraptera: Philopteridae sensu lato), with description of a new species - Cicchino, Armando C.; Valim, Michel P.; González-Acuña, Daniel (Zootaxa, 2014)
We studied a collection of lice from Argentina, Brazil, Paraguay and Chile containing all four known species and one new species (described herein) in the genus Tinamotaecola, parasites of birds of the families Cariamidae and Tinamidae. We also (1) describe previously unknown second and third nymphal instars of two Tinamotaecola species, (2) discuss hosts and geographical ranges for all Tinamotaecola species, and (3) speculate on possible macroevolutionary events that may explain the current distribution of these lice on their respective avian hosts.